Benzene and cyclohexane separation using 1-butyl-3-methylimidazolium thiocyanate - Gonfa, G. (American Institute of Physics Inc., 2017)
Cyclohexane is mainly produced by catalytic hydrogenation of benzene. Removal of unreacted benzene from the product stream is very important in this process. However, due to their close boiling points and azeotrope formation, it is very difficult to separate cyclohexane and benzene by conventional distillation. Currently, special separation processes such as processes extractive distillation is commercially used for this separation. However, this extractive distillation suffers from process complexity and higher energy consumption due to their low extractive selectivity of molecular entrainers used. The aim of the present work is to investigate the applicability of ionic liquids as entrainer in extractive distillation of benzene and cyclohexane mixture. In this study, we investigated 1-butyl-3-methylimidazolium thiocyanate (BMIMSCN) ionic liquid for separation of benzene and cyclohexane by measuring the Vapor Liquid Equilibrium data of the two components in the presence of the ionic liquid. As green and potential environmentally friendly solvents, ionic liquids have attracted increasing attention as alternative conventional entrainers in extractive distillation. Isothermal Vapor Liquid Equilibrium for the benzene + cyclohexane + BMIMSCN ternary system was obtained at 353.15 K using a Head Space Gas Chromatography. The addition of BMIMSCN breaks the benzene-cyclohexane azeotrope and increased the relative volatility cyclohexane to benzene in the mixture. The effect of BMIMSCN on the relative volatility cyclohexane to benzene was studied at various benzene and cyclohexane compositions and solvent to feed ratios. The performance of BMIMSCN was compared with typical conventional solvents, dimethylformamide (DMF) and dimethylsulfoxide (DMSO). The results show that the relative volatility of cyclohexane to benzene in the presence of BMIMSCN is higher compared that of DMSO and DMF. © 2017 Author(s).